An Analysis of Local Wisdom in the Discourse of Indonesian Folklore “Batu Menangis” - Titi Rokhayati; Tria Oktafiana; Ja’far Sodiq; Edi Sunjayanto (English Education and Literature Journal (E-Jou), 2026)
This study investigates the local wisdom within the Indonesian folklore Batu Menangis using the methods of coherence and cohesion. The narrative, originating from Kalimantan Barat, serves as a medium to explore traditional values such as filial piety, humility, and respect for one's origins. By analyzing its narrative structure, thematic connections, and linguistic features, the research highlights how coherence devices (e.g., repetition, conjunctions) and logical sequencing establish coherence within the text. This folklore is important to be analyzed because it is cultural context that carries local wisdom, moral education and gender values, social norms and intercultural meaning that are highly relevant to education, linguistics, literature and cultural studies today. The findings reveal that the story reflects cultural norms, moral lessons, and societal expectations, which symbolized through the transformation of the disobedient child into a crying stone. The study emphasizes the role of Batu Menangis in preserving Indonesia's cultural heritage and promoting educational values. Through a detailed examination of its local wisdom, the research underscores the importance of folklore as a vehicle for cultural transmission and moral education. This research highlights the discourse analysis and the importance of integrating folklore into educational contexts to strengthen character education and cultural literacy. By uncovering the local wisdom embedded in Batu Menangis, the study contributes to broader discussions on preserving intangible cultural heritage and utilizing traditional narratives as meaningful pedagogical resources in contemporary education